An education model to empower women in tech entrepreneurship - Paiva, Teresa; Felgueira, Teresa; Alves, Catarina; Gomes, Natalia; Salgado, Sofia; Salaberri, Marcelo (Frontiers in Education, 2024)
Introduction The gender gap in technology entrepreneurship represents a significant and persistent disparity, with women significantly underrepresented in creating and leading technology start-ups. To address this multifaceted problem, it is critical to research and implement educational models that can foster intrinsic motivation in aspiring female entrepreneurs. Self-Determination Theory (SDT) provides a valuable framework for such an educational approach, emphasizing the importance of satisfying essential psychological needs—autonomy, competence and relatedness—to enhance motivation and commitment. Integrating SDT principles into entrepreneurship education can create supportive environments that empower women, encourage diverse perspectives, and ultimately bridge the gender gap in tech entrepreneurship. Particularly in the case of female students, it is important to understand how to empower their behavior choices to make possible different professional paths, with tech entrepreneurship being one of them. This gender gap has not yet been addressed through an education model proposal. Much has been said to characterize and identify it, but there is no proposal to change the higher education system in the STEM area, which is the research goal achieved in this paper: we need to analyze the gender gap in HEI and its relation to becoming entrepreneurial and understand how HEI may support the tech entrepreneurial behavior. To answer these questions we are going, in pursuit of the intrinsic motivations to support more entrepreneurial behavior in STEM female students. Methods A quantitative approach was designed to collect data to identify the gender gap in five European higher education institutions (HEI) in five different countries. In April, surveys were launched to female students, allowing a descriptive, exploratory factor analysis and structural equation modeling to test the SDT intrinsic motivation constructs. Results The results confirmed that there is a gender gap to overcome and that the teaching-learning process may help to potentiate the female student’s capacities of self-knowledge and self-value for female students. The autonomy need was identified as the most influential construct on students becoming entrepreneurs, not dishing the effect the competences and relatedness have. Understanding this reality allows for further development of the education model proposed and discussed. Conclusion Higher education lectures, particularly in STEM programs, can improve their teaching processes to become more inclusive and promote an effective entrepreneurial mindset. Understanding what will change helps engage in a different paradigm of education in technology, demystifying the concepts of entrepreneurship and allowing inclusion and gender equality in the higher education system.